Pengaruh Variasi Desain Crash Box Pola Origami terhadap Kemampuan Penyerapan Energi - Kusyairi, Imam; Agus Choiron, Moch.; Purnowidodo, Anindito (ROTOR, 2015)
This study developed crash box design on origami patterns. These typically have got the dents whichserve as pre-folding. Therefore, the collapses modesarepredictable and stable. The geometry variation of crash box comprises four factors, i.e. basin length (c), distance between the basins (b), thickness (t) and number of segments (M). Meanwhile, the design of optimal variations utilized L9 Taguchi and deformas pattern analysis. The method of this study used software finite and the element of crash box modelling consists of three components, e.g. impactor, crashbox, and fixed support. The material used is AA7003-T7 modellingas thebilinear isotropic hardening. Model loading waconveyed 64 km/h on the impactor. The research shows that the response of quality characteristics of energy absorption is the larger the better. The energy absorption respectively covered 1)thickness (t), 2) segment (M), 3) distance between basins (b), and 4) basin length (c).Whereas, the highest energy absorption of the crash box occupied by the origami pattern no. 3 with c = 9 mm, b = 60 mm, t = 2 mm and M = 6, Â reaching 7,247,826 J. In fact, the deformation behavior of the model no. 3 tends to have a symmetrical deformation without buckling. Keywords:Crash box, origami, energy absorbed,deformation